Legal Problem of the Merah Putih Cooperativ - Muhammad Alif Fauzi; Muh. Ali Masnun; Ainun Najwa (Universitas Negeri Surabaya, 2026)
The Merah Putih Cooperative is a government program aimed at strengthening the village economy through cooperative institutions based on economic democracy and family principles. This study aims to analyze the legal basis for the establishment of the Merah Putih Cooperative, the legal challenges in its implementation, and the potential criminal risks for cooperative managers. The study uses a normative juridical method with a statutory, conceptual, and analytical approach. The results show that the establishment of the cooperative based solely on Presidential Instruction Number 9 of 2025 does not meet the legality principles of state administrative law, thus creating legal uncertainty. In addition, there is overlapping function between the cooperative and the Village-Owned Enterprises (BUMDes), which causes institutional conflict at the village level. Weak internal oversight and low capacity of cooperative managers also increase the potential for misuse of funds, corruption, and other legal violations. Therefore, strengthening formal regulations, harmonizing village institutions, and improving cooperative governance are needed so that the Merah Putih Cooperative program can run transparently, democratically, and sustainably.